Proceedings of 2018 Chinese Intelligent Systems Conference Volume I - Jia, Yingmin; Du, Junping; Zhang, Weicun; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
These proceedings present selected research papers from CISC'18, held in Wenzhou, China. The topics include Multi-Agent Systems, Networked Control Systems, Intelligent Robots, Complex System Theory and Swarm Behavior, Event-Triggered Control and Data-Driven Control, Robust and Adaptive Control, Big Data and Brain Science, Process Control, Nonlinear and Variable Structure Control, Intelligent Sensor and Detection Technology, Deep learning and Learning Control Guidance, Navigation and Control of Flight Vehicles, and so on. Engineers and researchers from academia, industry, and government can get an insight view of the solutions combining ideas from multiple disciplines in the field of intelligent systems.
Research on Cosine-type Non-uniform Air Gap Structure Based on Finite Element Analysis -- Quasi-Interval Bipartite Consensus Problems on Discrete-Time Signed Networks -- The Research on Force-Magnetic Effect of Wheelset of High-speed Train Based on Metal Magnetic Memory Method -- Application of single neuron LADRC in trajectory tracking control of parafoil system -- A design scheme of adaptive switching neural control with uncertain nonlinearity and external disturbance.
Keywords: Computational intelligence; Artificial intelligence; Control engineering; Robotics; Automation; Computational Intelligence; Artificial Intelligence; Control, Robotics, Automation